2008
DOI: 10.2147/btt.s1852
|View full text |Cite
|
Sign up to set email alerts
|

Review of consensus interferon in the treatment of chronic hepatitis C

Abstract: Consensus interferon (CIFN) is an artificially engineered interferon that reflects most of the human genotype 1 interferons and shows a higher biological and antiviral capacity in vitro. It has been used internationally to treat patients with chronic hepatitis C (HCV) infection before pegylated IFN became available. To mimic the half-life of PEG-IFN it has to be administered on a daily basis. The gold standard in the treatment of hepatitis C is well established and recommended. Today patients are being treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…*, **, significantly different from after Mal values (* P<0.05; ** P<0.01). Low dose administration of IFN- is defined as IFN- administration with the amount of 0.05-1000 IU/kg, compared to high dose administration of IFN-, which is one of the traditional treatments by intramuscular or subcutaneous injection applied to hepatitis C, uses several hundreds to ten million IU/kg [39]. Human IFN- (HuIFN-) has been given orally in low doses to treat or prevent a number of infectious and immune-based diseases in a variety of species [2,7,14,26].…”
Section: Discussionmentioning
confidence: 99%
“…*, **, significantly different from after Mal values (* P<0.05; ** P<0.01). Low dose administration of IFN- is defined as IFN- administration with the amount of 0.05-1000 IU/kg, compared to high dose administration of IFN-, which is one of the traditional treatments by intramuscular or subcutaneous injection applied to hepatitis C, uses several hundreds to ten million IU/kg [39]. Human IFN- (HuIFN-) has been given orally in low doses to treat or prevent a number of infectious and immune-based diseases in a variety of species [2,7,14,26].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated a higher anti-viral activity against vesicular stomatitis virus (VSV) of CIFN compared with IFN-a2a or 2b (Ozes et al, 1992). Clinical studies with therapy-naive chronic HCV patients treated with CIFN plus ribavirin showed more SVR than with standard treatment (reviewed in Witthoft 2008) . However, due to its short half-life, CIFN has to be administered daily, which is an obvious disadvantage for clinical use.…”
Section: New Ifnsmentioning
confidence: 99%
“…A combined treatment including Peginterferon Alfa-2a/Ribavirin with or without protease inhibitor has become the standard course for the treatment of CHCV infection [10]. The efficacy of treatment depends on several factors such as baseline viral load, severity of liver disease, body weight, ethnicity and viral genotype with type 1 appearing to be less responsive to treatment than other types [44]. However, only about half of treated patients achieve a sustained virology response (SVR) in which serum HCV RNA become undetectable for at least 6 months after cessation of therapy.…”
Section: Introductionmentioning
confidence: 99%